Modification of α,β-conjugated enol-keto containing compound towards to the synthesis of ethyleneimine compound and its complexes with Co(II) - Ong, Cheng Guan (Universiti Malaysia Sarawak (UNIMAS), 2012)
This project was aimed to synthesize the allylideneamine moiety ligand in order to replace the phenylpyridine (ppy) moiety ligand in the metallacycle complexes. The L series compounds were synthesized by reacting p-(R)-acetophenone (R = H or NO2) to glyoxal through cross-adol condensation reaction. Then, three S series compounds were synthesized by adding 2-aminophenol into the L series compounds using Schiff base synthesis reaction. Two of the S series compounds namely S1 and S2 were not obtained in the synthesis; indeed, another product namely S4 was obtained from the reaction of remaining glyoxal and 2-aminophenol. Two Co2+ complexes were prepared from the reaction of respective S4 and S3 compounds to CoCl2 at room temperature and the spectroscopic data from NMR, IR and UV were obtained. There are some changes found in the IR, 1H NMR and UV-visible spectra of complexes compared to their free ligand. The conductivity studies showed that the oxidation states of the complexes were remained at +2 oxidation state and all complexes are neutral complex.